Contribution of livestock farming systems to the nitrogen cascade and consequences for farming regions. (October 2014) - Cellier, P.; Rochette, P.; Durand, P.; Faverdin, P.; Kuikman, P. J.; Peyraud, J.-L.
<x content-type="archive" xml:space="preserve">Abstract</x> This article describes the nitrogen flows in the environment and points to the specificities of the livestock production. Till the beginning of the 20th century, the symbiotic fixation and the recycling of animal excreta supplied the nitrogen necessary for the fertility of soil. In 1913, the Haber-Bosch process allowed the industrial synthesis of ammonia and made possible the fertilisation without association of crop production with the livestock farming. The efficiency of the nitrogen in livestock farming is low with nearly half or more of the inputs losses to the environment. These losses have diverse impacts that intervene at various spatial scales owing to the nitrogen cascade. Quantitative assessment of nitrogen flows at the scale of regions started in the early 1980s in Western Europe and North America. These studies provided estimates of the spatial variability of nitrogen discharge within a region. They confirmed the differences between areas with a high animal density such as Brittany (western region, France) and other regions. It was also found that the same nitrogenous losses could lead to different levels of environmental impacts according to the sensibility of a given environment and its capacity to cope with nitrogen excess. Climate, soils characteristics, animal density, and proportions of agricultural land under annual and perennial crops are drivers of this sensibility.